Effects of Bee Bread Microencapsulation with Biopolymers Using Spray Drying Technique - BINTI MOHAMAD, NASHA ELINA; Mansur, Sity Aishah (Progress in Engineering Application and Technology, 2025)
Bee bread (BB) is one of natural products from bees that is consumed for its nutritional and health benefits. BB contains abundance of proteins, flavonoids, and phenolics. These bioactive compounds are sensitive and easily degraded over time. Therefore, effective encapsulation is essential to reserve these compounds. In this study, the spray drying technology is used to encapsulate BB with biopolymers like xanthan gum, arabic gum, chitosan, and sodium alginate to retain its nutritional value. Several formulations of BB. : biopolymers were prepared and solution was put into a spray dryer with an inlet temperature of 160°C to 170°C and a flow rate of 7 to 12 rpm. Using spray drying technique, there was only 45% of microencapsulated BB collected. Microencapsulation efficiency, total protein, total flavonoid content (TFC), total phenolic content (TPC) and antioxidant test such as DPPH and FRAP assays were assessed. The highest value of total protein is 661.863 µg/g in sample 20, in sample 10 contain the highest TFC and TPC values which are 11.266 mg QE/g and 32.026 mg GAE/g, respectively. For antioxidant test, DPPH test shows 76.7% of IC50 in sample 4while for FRAP assays shows 2259.6 mg AAE/g in sample 18. Additionally, test using FTIR and SEM were performed to examine the microstructure and functional qualities of encapsulated BB . In conclusion, spray drying technique with biopolymers, xanthan gum, arabic gum, sodium alginate, and chitosan can be found in all sample where it successfully encapsulated BB while providing a protective structure for its bioactive components.